Differential sensitivity of radionuclide ventriculography for the detection of anterior and inferior infarction. Issue 5 (November 1988) - Underwood, S R; Walton, S; Laming, P J; Ell, P J; Emanuel, R W; Swanton, R H
Abstract : Attenuation of counts from the more distant inferior portion of the left ventricular blood pool in equilibrium radionuclide ventriculography may mean that inferior infarction is less likely to be detected than anterior infarction. Fourier amplitude and phase images can be used to map the extent and timing of regional ventricular wall motion and this study assesses their use for the detection of anterior and inferior infarction. Normal regional values of amplitude and phase were established in 38 individuals without evidence of cardiac abnormality. In 20 patients with anterior infarcts, though the sensitivity of the combined left anterior oblique amplitude and phase images was high (95%) it was lower (77%) in 39 with inferior infarcts, principally because the sensitivity of the phase image for the detection of inferior infarcts was only 39%. Right anterior oblique images generated from a first pass study detected all 13 patients with inferior infarcts. The mean left ventricular ejection fraction was significantly lower in the patients with anterior infarcts (37%) than in those with inferior infarcts (48%). Although the mean wall motion score on x ray contrast ventriculography was slightly lower in the patients with anterior infarction, the high sensitivity of the right anterior oblique amplitude and phase images in inferior infarction suggests that attenuation of counts is an important cause of reduced sensitivity of the left anterior oblique images. This may also partly explain the lower ejection fractions in inferior infarction. It follows that both a right anterior oblique first pass study and a left anterior oblique equilibrium study are necessary for an accurate description of regional wall motion.